Spór o interpretację. Krytyka sufizmu z pespektywy salafizmu - Januszkiewicz, Jan (Humaniora. Czasopismo Internetowe, 2025)
The purpose of this paper will be to compare two extremely opposite movements within Islam – Sufism and Salafism, and more specifically to analyze one of them from the perspective of the representatives of the latter. As we shall see, this is essentially a dispute within theological hermeneutics, in which two models of interpretation meet. One emphasizes the validity of a literal interpretation of the text, while the other emphasizes an invention-based, spiritual, subjective interpretation. The latter model of interpretation is appropriate to Sufi mysticism. Defining Sufism and Salafism by contrasting them to official currents in Islam is not entirely appropriate. In the case of Sufism and Salafism, we are not dealing with factions of Islam, but with different interpretations of it, since the difference between them lies not in the difference of professed dogmas, which are fixed and unchangeable, but in lifestyle and philosophy. It is a clash between orthodox fundamentalism and mysticism. I base my work on the fatwas of ‘Abd al-Azīz ibn Bāz, a Saudi cleric and former grand mufti of Saudi Arabia.